3. EVALUATION OF THE EFFECTS OF REGULATING EXOGENIC BLOOD LIPID DISORDERS OF HARD CAPSULES “TIEU TICH GIANG PHI - HV” IN WHITE RATS (Vietnam Journal of Community Medicine, 2024)
Objectives: To evaluate the adjusting effects of external dyslipidemia of  “Tiêu tích giáng phì - HV” capsules in white rats.Research objects and methods: Following the model of Nassiri et al (2009), with improvements according to Nguyen Trong Thong et al (2014), Wistar white rats were induced lipid disorders with cholesterol oil (10 ml/kg/24h dose). Evaluation index: triglycerides, total cholesterol, high density lipoproteins cholesterol, low density lipoprotein cholesterol, very low density lipoprotein cholesterol, atherosclerotic index at times 0, 14 and 28 days. Data were processed by SPSS 20.0 software.Results: The group that used the drug at a dose of 442.8 mg/kg/day (expected human dose), reduced total cholesterol, low density lipoprotein cholesterol and atherosclerotic index compared to group 2 after 4 weeks (p < 0.05). In the group using the drug at a dose of 1328.4 mg/kg/day, total cholesterol, triglycerides, low density lipoprotein cholesterol, very low density lipoprotein cholesterol, and atherosclerotic index indexes all had statistically significant differences after 4 weeks (p < 0.05).Conclusion: Both reagent doses have good effect in treating dyslipidemia in white rats.
Keywords: Dyslipidemia, white rats, foliumnelumbinis, pericarpium citri.